Le temps du développement en Palestine - Sbeih Sbeih (Temporalités)
By analyzing an agricultural development project realized by a multiplicity of local actors, in particular NGOs, under the aegis of an international agency, the article studies the temporality of development in Palestine. Built around the idea of a prosperous future and based on economic rationality, the temporal conception of development consists of breaking with the past and entering into opposition with colonial temporality weighed down by uncertainties. It emphasizes the skills of the “professionals of development” and their ability to master time. By transforming uncertainty into a measurable risk, they adopt working methods that ignore the actual experiences of the actors and beneficiaries of the project. This temporal conception extends to cover the entire social space created by collective projects financed by donors: the world of development. Without making any reference to domination or the colonial situation, these projects trace the history of that world. Though it is perceived as truth by the “developers”, who have incorporated the meaning of development, it proves to be an illusion for those who conceive reality through the uncertainty that disrupts their daily lives.